2013
DOI: 10.1039/c3nr04883g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nickel nanoparticle size in an organic/metal–organic matrix through the use of different solvents

Abstract: (2013) 'Controlling nickel nanoparticle size in an organic/metal-organic matrix through the use of di erent solvents. ', Nanoscale., 5 (24). pp. 12212-12223. Further information on publisher's website:http://dx.doi.org/10.1039/c3nr04883gPublisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous work by us on nominal Ni 2 A salts showed that, when swapping the TCNQ for tetrafluro-TCNQ (TCNQF 4 ), a black powder was formed with similar magnetic properties to that observed within Ni 2 TCNQ [13]. However, the magnetic properties showed a solvent dependency and when a nitrilebased solvent was used, this caused there to be a significant change in the room temperature magnetism.…”
Section: Introductionmentioning
confidence: 93%
“…Previous work by us on nominal Ni 2 A salts showed that, when swapping the TCNQ for tetrafluro-TCNQ (TCNQF 4 ), a black powder was formed with similar magnetic properties to that observed within Ni 2 TCNQ [13]. However, the magnetic properties showed a solvent dependency and when a nitrilebased solvent was used, this caused there to be a significant change in the room temperature magnetism.…”
Section: Introductionmentioning
confidence: 93%
“…Ni nanoparticles encapsulated in a carbon matrix, Ni@C nanocomposites, were investigated in Refs. [20][21][22][23][24][25][26][27][28]. Depending on used synthetic techniques, Ni@C nanocomposites can have different carbon structures, morphology and magnetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all prior works dedicated to the investigation of Ni@C nanocomposites [24][25][26][27] point at the lower values of saturation magnetization comparing to that of bulk Ni. The possible reasons of magnetization reduction with decrease in nanoparticle size are discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%